Alexandria antiqua : a topographical catalogue and reconstruction - Abdo, Amr, (Archaeopress Archaeology, 2022)
'Alexandria Antiqua' aims to catalogue the archaeological sites of Alexandria, from the records of the French Expedition (1798-99) to the present day, and to infer the urban layout and cityscape at the time of its foundation (4th century BC), and then through the successive changes which took place up to the Arab conquest (7th century AD).